2021
DOI: 10.3389/fmars.2021.669748
|View full text |Cite
|
Sign up to set email alerts
|

Humpback Whale (Megaptera novaeangliae) Song on a Subarctic Feeding Ground

Abstract: Male humpback whales (Megaptera novaeangliae) are known to produce long complex sequences of structured vocalizations called song. Singing behavior has traditionally been associated with low latitude breeding grounds but is increasingly reported outside these areas. This study provides the first report of humpback whale songs in the subarctic waters of Northern Norway using a long-term bottom-moored hydrophone. Data processed included the months January–June 2018 and December 2018–January 2019. Out of 189 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Darling et al (2019aDarling et al ( , 2022 concluded that these observations are indicative of ocean basin-wide panmixia, on the assumption that they could only result from extensive exchange of singing males between wintering areas. However, though singing was once thought to be largely confined to wintering grounds (Charif et al, 2001;Clapham & Mattila, 1990), we now know that humpback whales sing both on their feeding grounds late in the season and on migration (Clark & Clapham, 2004;Magnúsd ottir et al, 2014;Mattila et al, 1987;Noad & Cato, 2007;Norris et al, 1999;Schall et al, 2022;Stimpert et al, 2012;Tyarks et al, 2021;Vu et al, 2012), providing a mechanism for transmission of songs among winter areas in the absence of direct exchange of individuals between wintering grounds (Garland et al, 2013;Owen et al, 2019). Rapid annual shifts in humpback whale song, called song "revolutions," have been attributed to exposure to song from other populations, either on the feeding ground or migratory route (Garland et al, 2011(Garland et al, , 2013Owen et al, 2019;Tyarks et al, 2022) or due to the movement of a small number of males between wintering areas (Allen et al, 2018;Noad et al, 2000).…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…Darling et al (2019aDarling et al ( , 2022 concluded that these observations are indicative of ocean basin-wide panmixia, on the assumption that they could only result from extensive exchange of singing males between wintering areas. However, though singing was once thought to be largely confined to wintering grounds (Charif et al, 2001;Clapham & Mattila, 1990), we now know that humpback whales sing both on their feeding grounds late in the season and on migration (Clark & Clapham, 2004;Magnúsd ottir et al, 2014;Mattila et al, 1987;Noad & Cato, 2007;Norris et al, 1999;Schall et al, 2022;Stimpert et al, 2012;Tyarks et al, 2021;Vu et al, 2012), providing a mechanism for transmission of songs among winter areas in the absence of direct exchange of individuals between wintering grounds (Garland et al, 2013;Owen et al, 2019). Rapid annual shifts in humpback whale song, called song "revolutions," have been attributed to exposure to song from other populations, either on the feeding ground or migratory route (Garland et al, 2011(Garland et al, , 2013Owen et al, 2019;Tyarks et al, 2022) or due to the movement of a small number of males between wintering areas (Allen et al, 2018;Noad et al, 2000).…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…This migration route and feeding ground off Norway's coast has shown to be shared with an interchange of different humpback breeding populations from Cape Verde (Africa) and the West Indies (America; Beŕubéet al, 2004;Stevick et al, 2016;Stevick et al, 2018;Whaletrack UiT, 2018;Wenzel et al, 2020). Given the identified humpback whale song occurrence in Northern Norway as described in Tyarks et al (2021), this might indicate a potential for acoustic interaction between the two breeding populations. Therefore, the aim of this study was to investigate the song structure and complexity and to find evidence of humpback whale song evolution on this subarctic feeding ground and migratory passage route.…”
Section: Introductionmentioning
confidence: 81%
“…Data used in this study were collected by Node 1(Equinor and IMR, 2020). Produced by Geir Pedersen and reprinted with permission fromTyarks et al, 2021 (Copyright 2021.…”
mentioning
confidence: 99%
“…The vocal repertoire of a species can be determined by both sex and sexual maturity, and the degree of vocalization may vary between seasons [ 25 , 53 55 ]. For example, while humpback whales produce many different types of social calls, only male humpbacks are known to produce highly complex, long-lasting songs associated with breeding and migration [ 54 , 56 , 57 ]. By contrast, male blue whales and fin whales produce simple low-frequency calls [ 2 , 22 , 52 ].…”
Section: Introductionmentioning
confidence: 99%